2023
DOI: 10.1111/apt.17631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social determinants of health on mortality and incident liver‐related events and cardiovascular disease in steatotic liver disease

Abstract: SummaryBackgroundSocial determinants of health (SDOH) are becoming increasingly recognised as mediators of human health. In the setting of metabolic dysfunction‐associated steatotic liver disease (MASLD), most of the literature on SDOH relates to individual‐level risk factors. However, there are very limited data on neighbourhood‐level SDOH in MASLD.AimTo assess whether SDOH impact fibrosis progression in patients who already have MASLD.MethodsThis was a retrospective cohort study of patients with MASLD seen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, emerging data suggest that neighbourhood-level SDOH may affect both the development and progression of SLD. 6,7 Chen et al 8 have expanded on this work by examining the association between two well established neighbourhood-level SDOH ('disadvantage' and 'affluence') and clinical outcomes among patients with metabolic dysfunction-associated SLD (MASLD) seen at a single centre in Michigan. Increased neighbourhood disadvantage was associated with higher mortality and incident cardiovascular disease (CVD); higher neighbourhood affluence was associated with lower mortality, CVD and liver-related events (LRE).…”
Section: Editorial: Social Determinants Of Health In Steatotic Liver ...mentioning
confidence: 99%
“…However, emerging data suggest that neighbourhood-level SDOH may affect both the development and progression of SLD. 6,7 Chen et al 8 have expanded on this work by examining the association between two well established neighbourhood-level SDOH ('disadvantage' and 'affluence') and clinical outcomes among patients with metabolic dysfunction-associated SLD (MASLD) seen at a single centre in Michigan. Increased neighbourhood disadvantage was associated with higher mortality and incident cardiovascular disease (CVD); higher neighbourhood affluence was associated with lower mortality, CVD and liver-related events (LRE).…”
Section: Editorial: Social Determinants Of Health In Steatotic Liver ...mentioning
confidence: 99%
“…The Five Times Sit-to-Stand Test is part of a short physical performance battery (SPPB) and is widely used to evaluate physical performance. 1,2 In this test, the time required to complete five consecutive rises from a chair is measured, and this action is performed as swiftly as possible, without arm assistance. As this test relates not only to self-reported disability but also to functional outcomes, [1][2][3] it is also used to diagnose sarcopenia.…”
Section: Funding Informationmentioning
confidence: 99%
“…1,2 In this test, the time required to complete five consecutive rises from a chair is measured, and this action is performed as swiftly as possible, without arm assistance. As this test relates not only to self-reported disability but also to functional outcomes, [1][2][3] it is also used to diagnose sarcopenia. [4][5][6] There are two different approaches to time the Five Times Sit-to-Stand Test: From a seated position, the test ends either in a fifth standing position (fifth stand) or in another fifth seated position (fifth sit).…”
Section: Funding Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the Centers for Disease Control and Prevention show higher prevalence of diabetes among non-White racial/ethnic groups; ( 10 ) based on national data, obesity is associated with lower household income and lower education level ( 16 ). Although the direct relationship between SDoH and MASLD is less well-studied, emerging evidence has shown that education ( 5 ) and race/ethnicity ( 4 ) are associated with MASLD prevalence and severity, neighborhood-level SDoH is associated with mortality, complications and cardiovascular disease, ( 26 ) and food insecurity is associated with increased risk of advanced liver fibrosis and all-cause mortality among those with MASLD ( Figure 1 ) ( 2 , 24 , 27–30 ).…”
Section: Introductionmentioning
confidence: 99%